Respuesta :

Option B:

[tex]$f^{-1}(x)=\frac{3-x}{14}[/tex]

Solution:

Given function is [tex]f(x)=3-14 x[/tex].

To find the inverse of the function:

Let y = f(x)

[tex]y=3-14 x[/tex]

Subtract 3 on both sides of the equation, we get

[tex]y-3=-14 x[/tex]

Divide by –14 on both sides of the equation.

[tex]$\frac{y-3}{-14} =\frac{-14x}{-14}[/tex]

[tex]$\frac{y-3}{-14} =x[/tex]

Negative sign in the denominator go to the numerator , we get

[tex]$\frac{3-y}{14} =x[/tex]

We know that y = f(x)   ⇒ [tex]x=f^{-1}(y)[/tex]

Substitute [tex]x=f^{-1}(y)[/tex]

[tex]$\frac{3-y}{14} =f^{-1}(y)[/tex]

Since the choice of the variable is arbitrary, we can write this as

[tex]$\frac{3-x}{14} =f^{-1}(x)[/tex]

[tex]$f^{-1}(x)=\frac{3-x}{14}[/tex]

Hence Option B is the correct answer.

ACCESS MORE